Neutrophil to Lymphocyte Ratio as a Predictor of Adverse Outcome in Patients with Decompensated Liver Cirrhosis - Valeriy D. Lunkov; Marina V. Maevskaya; Ekaterina K. Tsvetaeva; Ana G. Mendez; Maria S. Zharkova; Petr E. Tkachenko; Vladimir T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The natural history of liver cirrhosis (LC) is characterized by two stages: compensated and decompensated. Current clinical and laboratory prognostic models, such as Child-Pugh and MELD scales, do not take into account immune dysregulation, as well as it potential impact on the LC decompensation and the survival. Neutrophil to lymphocyte ratio (NLR) is simple and affordable parameter, representing the imbalance of two distinct immune pathways.Aim: to evaluate relationship between NLR level, mortality and SIRS development in patients with DC.Materials and methods. In this retrospective study 36 patients with DC which were hospitalized in Hepatology Department of V.H. Vasilenko clinic of propaedeutics and internal diseases, gastroenterology and hepatology, Sechenov University from January 2009 to December 2017 were enrolled. Correlation analysis, univariate and multivariable analysis were provided to find factors statistically significantly associated with lethal outcome and SIRS. The optimal cut-off levels for the NLR associated with adverse outcome were determined.Results. AIn multivariable analysis, NLR > 4 (p < 0,001) was statistically significantly associated with lethal outcome in patients with DC during hospitalization (OR: 1.57, [95 % CI 1.125–2.209], p = 0.008). Sensitivity and specificity of this cut-off is 100 % and 79.17 %, respectively. NLR > 4.8 was associated with SIRS development during hospitalization (OR: 1.484, [95 % CI 1.103–1.997], p = 0.009) with 100 % sensitivity and 90 % specificity.Conclusions. NLR is an independent risk factor of lethal outcome and SIRS development in patients with decompensated liver cirrhosis.